Research on tool axis vector optimization when face milling complex surfaces - Zhao, Pengrui; Liu, Zhifeng; Li, Zhixiong; Cao, Zirui (International journal of advanced manufacturing technology, 2023)
In 5-axis machining, the existing tool’s axis vector optimization methods are limited since they only consider the global collision between the tool and the workpiece while aiming at the ball-nosed cutter. A multi-factor vector optimization method for the face milling cutter shaft is proposed to solve this problem. This method comprehensively considers machining global collision, cutting force, the angular displacement of a rotating shaft, and angular speed. An improved global collision detection method of cutter axis vector based on the NURBS surface principle is developed, and a global collision detection algorithm is employed to determine the cutter machining global collision. The relationship model between the end-milling cutter axis vector and cutting force variation is established to optimize the cutting force. In addition, an optimization model of angular displacement and velocity of the machine tool’s rotating axis is proposed based on Dijkstra optimal path algorithm. The CAM software simulation and experimental validation are conducted using a large propeller with a complex surface. The tool’s axis vector optimization algorithm is applied to the propeller results. Comparing the tool’s axis vector optimization results to those obtained without optimization, it is discovered that the surface workpiece’s machining quality has significantly increased.